Structural New Data for Mitochondrial Peroxiredoxin From Trypanosoma cruzi Show High Similarity With Human Peroxiredoxin 3: Repositioning Thiostrepton as Antichagasic Drug - Rivera-Santiago, Lucio; Martínez, Ignacio; Arroyo-Olarte, Ruben; Díaz-Garrido, Paulina; Cuevas-Hernandez, Roberto I.; Espinoza, Bertha (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosoma cruzi, the causal agent of Chagas disease, has peroxiredoxins expressed in all stages of the parasite and whose function is to detoxify oxidizing agents, such as reactive oxygen species (ROS). These proteins are central for the survival and replication of the parasite and have been proposed as virulence factors. Due to their importance, they have also been considered as possible therapeutic targets, although there is no specific drug against them. One of them, the mitochondrial peroxiredoxin (TcMPX), is important in the detoxification of ROS in this organelle and has a role in the infectivity of T. cruzi. However, their structural characteristics are unknown, and possible inhibitors have not been proposed. The aim was to describe in detail some structural characteristics of TcMPX and compare it with several peroxiredoxins to find possible similarities and repositioning the antibiotic Thiostrepton as a potential inhibitor molecule. It was found that, in addition to the characteristic active site of a 2-cys peroxiredoxin, this protein has a possible transmembrane motif and motifs involved in resistance to hyper oxidation. The homology model suggests a high structural similarity with human peroxiredoxin 3 (PRX3). This similarity was corroborated by cross-recognition using an anti-human PRX antibody. Additionally, molecular docking showed that Thiostrepton, a potent inhibitor of human PRX3, could bind to TcMPX and affect its function. Our results show that Thiostrepton reduces the proliferation of T. cruzi epimastigotes, cell-derived trypomastigotes and blood trypomastigotes with low cytotoxicity on Vero cells. We also demonstrated a synergic effect of Thriostepton and Beznidazol. The convenience of seeking treatment alternatives against T. cruzi by repositioning compounds as Thiostrepton is discussed.